Centro de acompañamiento para pacientes con Cáncer Neiva Huila (2020)
This research contemplates the problem that lies in all those cancer patients who have not received adequate psychological and motor treatment, since those who go through this event have a high mortality rate, being one of the most difficult diseases eradicate the human body. Throughout the world there are health care centers for cancer, their levels of care are based on medical prognoses and solutions, but in reality if a person does not fight cancer or is defeated, what happens? WHAT IS IT? which accompaniment centers exist for these people in which way they face that duel. Taking this into account in the city of Neiva they maintain a medical care process similar to that which can be presented in any other city, and upon visualizing this it was concluded that the research process with an inductive methodology with a type of descriptive research, in the which we found the high rate of people who die annually in the department due to cancer. Given this, an architectural solution of an equipment is represented in a place of great potential due to its climate, social environment, terrain, the place is located in the town of Ulloa, with a precise environment for an accompaniment center for those who seek to find a concept different from what clinics normally are, a design based on the patient's social need for integration and how to face the fear and pain of this disease.